Experimental assessment of the impact of the introduced parasitoid Gyranusoidea tebygi Noyes on the mango mealbug Rastrococcus invadens Williams, by physical exclusion - Boavida, C.; Neuenschwander, Peter; Herren, H. (Elsevier, 1995)
The parasitoid Gyranusoidea tebygi Noyes was released in West Africa against the mango mealybug, Rastrococcus invadens Williams, a pest that invaded Africa in the early 1980s. The ability of G. tebygi to control the mango mealybug was assessed in mango trees using paired sleeve cages. In sleeve cages left open to allow parasitoid attack, G. tebygi reduced mealybug levels 2.7-fold within 1.5 host generations, compared to the closed-sleeve treatment. A parasitism index of 34.4% was measured in the open-sleeve treatment. On leaves without sleeves, the parasitism index was a-fold higher, and the mealybug population level was two times lower than that in the open-sleeve treatment. The lower level of the mealybug population on uncaged leaves, compared to the one on leaves protected by open cages, is attributed to higher mortality caused both by parasitism and by abiotic factors such as rain and wind. The potential of G. tebygi to reduce mango mealybug populations is therefore assumed to be higher than the paired sleeve treatments suggest.